2006
DOI: 10.1074/mcp.t500017-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Brain Plasma Membranes Isolated by Affinity Two-phase Partitioning

Abstract: A comprehensive analysis of plasma membrane proteins is essential to in-depth understanding of brain development, function, and diseases. Proteomics offers the potential to perform such a comprehensive analysis, yet it requires efficient protocols for the purification of the plasma membrane compartment. Here, we present a novel and efficient protocol for the separation and enrichment of brain plasma membrane proteins. It lasts only 4 h and is easy to perform. It highly enriches plasma membrane proteins and can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 39 publications
1
95
1
Order By: Relevance
“…The coupling of 2-DE with other analytical techniques has been reported to overcome some of the drawbacks of SDS-PAGE, e.g., difficulties in detecting low abundance proteins, aggregation of proteins, particularly hydrophobic proteins and reproducibility issues, by adding a preliminary analytical step. Some examples include a non-denaturing anion exchange chromatography prior to 2-DE to simplify the proteome and detect functional associations between proteins [30], and a pre-fractionation/concentration step using affinity partitioning in ATPS prior to 2-DE-LC/MS for membrane proteins enrichment [31]. It has been recently reported that optimized ATPS can serve as a presorting stage in proteomic studies since it can be customized for selective extraction and/or partition of large fractions of proteins from crude extracts.…”
Section: Atps and 2d Electrophoresis For 3d Characterization Of Proteinsmentioning
confidence: 99%
“…The coupling of 2-DE with other analytical techniques has been reported to overcome some of the drawbacks of SDS-PAGE, e.g., difficulties in detecting low abundance proteins, aggregation of proteins, particularly hydrophobic proteins and reproducibility issues, by adding a preliminary analytical step. Some examples include a non-denaturing anion exchange chromatography prior to 2-DE to simplify the proteome and detect functional associations between proteins [30], and a pre-fractionation/concentration step using affinity partitioning in ATPS prior to 2-DE-LC/MS for membrane proteins enrichment [31]. It has been recently reported that optimized ATPS can serve as a presorting stage in proteomic studies since it can be customized for selective extraction and/or partition of large fractions of proteins from crude extracts.…”
Section: Atps and 2d Electrophoresis For 3d Characterization Of Proteinsmentioning
confidence: 99%
“…This dissection can take place on the anatomical level (by analyzing defined brain regions instead of whole brain samples), on the subcellular level (by fractionation according to protein localization within a cell), on the biochemical level (according to protein pI, M r , solubility, hydrophobicity etc. ), or by a combination of these methods [95,100,[104][105][106][107]. In theory, information gained from screening the subproteomes can then be merged, eventually approximating complete coverage of the brain proteome.…”
Section: Proteome Mappingmentioning
confidence: 99%
“…Chromatography-based approaches, such as SDS-PAGE coupled to LC-MS/MS or multidimensional LC-MS/MS, are rapidly gaining popularity as fast and reliable methods for high-throughput protein identification [97][98][99][100]. Although impervious to many of the 2-DE shortcomings, the number of proteins identified in LC-based studies is usually between several hundred and a few thousand [66,98,101].…”
Section: Proteome Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction of the sample complexity by pre-fractionation represents a possible solution to this problem. Several pre-fractionation protocols have been developed that are applicable to brain tissue, including those suitable for plasma membrane proteins, which may be most interesting to neuroscientists (Li et al, 2004;Guillemin et al, 2005;Schindler et al, 2006Schindler et al, , 2008. Separating the proteome into less complex sub-fractions is generally limited by the amount of starting tissue available, as each separating step involves loss of proteins.…”
Section: Limitations and Drawbacks Of The Techniquementioning
confidence: 99%